Other Voices : a Study of the Late Poetry of Luis Cernuda - Coleman, Alexander (Studies in the Romance languages and literatures, 2018)
Coleman begins his book with the following supposition: that Luis Cernuda was a poet whose primary impulse in his art was the suppression of the subjective and the consequent objectivization of poetry.